2010
DOI: 10.1111/j.1365-277x.2010.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Practical limitations to a positive deviance approach for identifying dietary patterns compatible with the reduction of cancer risk

Abstract: The basis for PD guidance for developing dietary recommendations for cancer prevention was strong across all social classes in Guatemala, marginal for Mexico and Scotland, and effectively impossible for the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…A total of 68% of those studies use mixed methods, 21% use quantitative methods, and 11% used qualitative methods. The normal PD approach covered studies that tackled issues including health care–associated infections (de Macedo et al, ; Marra et al, ), enhancing health outcomes of women in disadvantaged circumstances (Long et al, ), cancer prevention (Vossenaar et al, ; Vossenaar, Bermúdez, Anderson, & Solomons, ), child marriage (Lackovich‐Van Gorp, ), child rearing (Aruna, Vazir, & Vidyasagar, ), infectious disease control (Babalola, ; Babalola et al, ; Nieto‐Sanchez, Baus, Guerrero, & Grijalva, ), improving pregnancy outcomes (Ahrari et al, ), counselling for family planning (Kim, Heerey, & Kols, ), child malnutrition (Aday, Hyden, Osking, & Tomedi, ; Bolles, Speraw, Berggren, & Lafontant, ; Guldan et al, ; Kanani & Popat, ; Merchant & Udipi, ; Merita, Sari, & Hesty, ; Roche et al, ; Sethi, Kashyap, Seth, & Agarwal, ; Shekar, Habicht, & Latham, ; Shekar, Habicht, & Latham, ; Wishik & Van Der Vynckt, ), neonatal mortality (Marsh et al, ), and managing medico‐social problems through self‐care (Gidado, Obasanya, Adesigbe, Huji, & Tahir, ).…”
Section: Positive Deviancementioning
confidence: 99%
“…A total of 68% of those studies use mixed methods, 21% use quantitative methods, and 11% used qualitative methods. The normal PD approach covered studies that tackled issues including health care–associated infections (de Macedo et al, ; Marra et al, ), enhancing health outcomes of women in disadvantaged circumstances (Long et al, ), cancer prevention (Vossenaar et al, ; Vossenaar, Bermúdez, Anderson, & Solomons, ), child marriage (Lackovich‐Van Gorp, ), child rearing (Aruna, Vazir, & Vidyasagar, ), infectious disease control (Babalola, ; Babalola et al, ; Nieto‐Sanchez, Baus, Guerrero, & Grijalva, ), improving pregnancy outcomes (Ahrari et al, ), counselling for family planning (Kim, Heerey, & Kols, ), child malnutrition (Aday, Hyden, Osking, & Tomedi, ; Bolles, Speraw, Berggren, & Lafontant, ; Guldan et al, ; Kanani & Popat, ; Merchant & Udipi, ; Merita, Sari, & Hesty, ; Roche et al, ; Sethi, Kashyap, Seth, & Agarwal, ; Shekar, Habicht, & Latham, ; Shekar, Habicht, & Latham, ; Wishik & Van Der Vynckt, ), neonatal mortality (Marsh et al, ), and managing medico‐social problems through self‐care (Gidado, Obasanya, Adesigbe, Huji, & Tahir, ).…”
Section: Positive Deviancementioning
confidence: 99%
“…In Mexico, an estimated 191,000 new cases of cancer are diagnosed annually ( AMLCC, 2023 ). A concordance analysis of selected WCRF/AICR recommendations for cancer prevention, which included 790 Mexicans aged 18–70 years, found that no participants adhered to the recommendations ( Vossenaar et al, 2010a ). In the same Mexican population, it was reported that no participants met the WCRF/AICR recommendations of body mass index (BMI) or daily intake of refined sugar ( Vossenaar et al, 2010b ).…”
Section: Introductionmentioning
confidence: 99%